E-Commerce for All: How Gen Z is Empowering MSMEs Towards Economic Resilience - Meitriana, Made Ary; Irwansyah, M. Rudi (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
Digital transformation is an urgent need for MSMEs in facing global economic dynamics. This study analyzes the role of Generation Z in empowering MSMEs through the adoption of e-commerce to strengthen economic resilience in Buleleng Regency, Bali. Using a quantitative approach with survey techniques of 384 respondents consisting of MSME actors and Gen Z entrepreneurs, this study measures the variables of digital literacy, e-commerce adoption, business innovation, and economic resilience. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 24.0 software. The results showed that Gen Z's digital literacy had a significant effect on the adoption of MSME e-commerce ([beta]= 0.567, CR = 8.924, p < 0.001). The adoption of e-commerce has been proven to increase business innovation ([beta] = 0.452, CR = 7.123, p < 0.001) which ultimately strengthens the economic resilience of MSMEs ([beta] = 0.634, CR = 9.876, p < 0.001). The research model explains 72.4% of the variance in the economic resilience of MSMEs. These findings provide theoretical contributions to the development of MSME digital transformation models and practical implications for technology-based economic empowerment policies.